In vivo anti-inflammatory activity, acute toxicity profiling, and sub-acute toxicity profiling of extracts from the fruit pulp and seeds of african baobab (Adansonia digitata L.) - Mercy Badu; Philip T. Thompson; Vivian E. Boamah (Scientific African)
Adansonia digitata (L.) is an ancient plant widely known for its diverse medicinal properties. The pulp and seeds of this plant are commonly consumed by rural populations in Africa, valued for their poly-therapeutic benefits. This study investigates the anti-inflammatory activity, acute toxicity, and sub-acute toxicity of extracts from the pulp and seeds using animal models. The anti-inflammatory potential was assessed using a carrageenan-induced foot edema model in 7-day-old chicks, while the acute and sub-acute toxicities were evaluated in Wistar albino rats. In the anti-inflammatory study, the fruit pulp extract exhibited an ED50 value of 282.12 mg/kg BW, while the seed extracts showed similar activity with ED50 values of 338.41 mg/kg BW for the polar extract and 347.40 mg/kg BW for the non-polar extract. In the acute toxicity evaluation, no mortality was observed at the highest administered dose of 5000 mg/kg BW, suggesting an LD50 value above the highest administered dose. Sub-acute toxicity studies over 28 days revealed significant increases (p < 0.05) in body weight, absolute organ weight, and relative organ weight in rats, yet without adverse effects on hematological or biochemical parameters. Histopathological analysis confirmed the absence of damage to kidney and liver tissues, indicating the safety of the extracts at doses below the estimated LD50. In conclusion, the extracts demonstrate notable anti-inflammatory activity and appear safe for consumption within the tested dose range, supporting their traditional use for health benefits.